Agronomic Biofortification of Zinc in Lentil - Karmakar, Mrinmoy; Sarkar, Narayan Chandra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted to study effect of zinc (Zn) application on growth, yield, Zn uptake and Zn use indices of lentil (Lens culinaris or Lens esculanta) during rabi (October to March)seasons 2016 and 2017 in red and lateritic soil of West Bengal, India. There were two main plot treatments i.e., crop establishment methods (zero tillage and conventional tillage) and seven sub-plot treatments i.e. levels of Zn and methods of application (seed coating @ 0.6% ZnSO4.7H2O, 1.2% ZnSO4.7H2O and 1.8% ZnSO4.7H2O, two foliar sprays @ 0.5% ZnSO4.7H2O, three foliar sprays @ 0.5% ZnSO4.7H2O, seed coating @ 1.2% ZnSO4.7H2O+two foliar sprays @ 0.5% ZnSO4.7H2O and control were laid out in split plot design replicated thrice. The crop establishment methods did not show any significant influence on growth, yield and nutrient uptake by lentil. However, among the levels of Zn and methods of application, seed coating @ 1.8% ZnSO4.7H2O produced significantly taller plants, more leaf area index, dry matter accumulation and yield. Regarding Zn concentration, combination of seed coating and foliar application @ 1.2% ZnSO4.7H2O+two foliar sprays @ 0.5% ZnSO4.7H2O resulted in significantly higher concentration than other treatments. Zn use efficiency was significantly higher (seed coating @ 1.2% ZnSO4.7H2O for agronomic efficiency and physiological efficiency, seed coating @ 0.6% ZnSO4.7H2O for partial factor productivity and seed coating @ 1.8% ZnSO4.7H2O for apparent Zn recovery) as compared to that of foliar application or combined application of seed coating and foliar spray.